LEARNING MANAGEMENT OF FAMILY EDUCATION THROUGH PARENTING CLASS TO IMPROVE PARENT’S POSITIVE PARENTING ABILITY (Case Study at PKBM Melati Jayagiri, West Bandung District) - indrayani indrayani (IKIP Siliwangi Bandung, 2018)
Abstract The main purpose of this study is to analyze the learning management of family education through parenting class to improve parent’s positive parenting ability conducted in Melati Jayagiri Community Learning Center (CLC/PKBM), Desa Jayagiri, Kecamatan Lembang, Kabupaten Bandung Barat.The study used qualitative approach and descriptive method. The research subjects were 5 persons, consisted of 3 community learning center’s students (WB1, WB2 and WB3) and triangulation from the informants coming from 1 CLC manager (P1) and 1 CLC educator (NS1). The study taken place in Melati Jayagiri Community Learning Center, Jayagiri Village, District Lembang, West Bandung regency. As the results of the study, the following data are obtained: 1) The lesson plans were designed by managers and educators after conducting needs assessments, after that learning objectives were determined, lessons and tools related to learning elements were prepared, 2) Parenting class was conducted with positive parenting as the main learning materials, and the supporting materials were conveyed in the form of storytelling, (b) the learning approach used was participative-andragogy, (c) the learning methods/ techniques used were discussions, lectures, practices and frequently asked questions and demonstrations, (d) the learning media were laptops, LCD, speakers (e) evaluation, (f) follow-up and (g) learning environment, 3) the Learning outcomes consisted of (a) cognitive, (b) affective,and (c) psychomotoric, all aspects indicating progressive improvement. The research recommends mutual wider partnership with other Early Childhood Education’s stakeholders for better management of this parenting class in the future.Keywords: family education, positive parenting, learning, management